EFEKTIFITAS PENERAPAN INSTRUMEN AKREDITASI LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) DI DINAS SOSIAL KABUPATEN SUMBAWA BARAT - WARDI, WARDI; UMAR, UMAR; HUSNI, HUSNI (Universitas Mahasaraswati K. Mataram, 2023)
This research discusses the effectiveness of the use of the Accreditation Instrument for Child Social Welfare Institutions (LKSA) in the West Sumbawa Regency Social Service. The objectives of this research consist of; 1) To find out the service efforts of the Child Social Welfare Institution (LKSA) in West Sumbawa Regency. 2) To analyze the effectiveness of the use of the Accreditation Instrument for Child Social Welfare Institutions (LKSA) at the West Sumbawa Regency Social Service. The research results showed that the use of the LKSA Accreditation Instrument has been effective as a reference in providing services and has had a positive impact on the development of LKSA in West Sumbawa Regency. By using the LKSA Accreditation Instrument, institutions are able to measure the quality of their services in order to improve children's welfare. Measuring the effectiveness of the use of the LKSA accreditation instrument in the West Sumbawa Regency Social Service using the Rasch Model shows that all participants are of the opinion that LKSA accreditation carried out by the West Sumbawa Regency Social Service provides additional knowledge and understanding of the substance and meaning of various legal/regulatory bases which serve as a reference in implementation. accreditation, providing additional abilities/skills in preparing accreditation. The implementation of the LKSA program at the West Sumbawa Regency Social Service using the Accreditation Instrument has been effective as a reference in providing services and has had a positive impact on the development of LKSA in West Sumbawa Regency. By using the LKSA Accreditation Instrument, institutions are able to measure the quality of their services in order to improve children's welfare